Comparative analysis in diagnosis by real‐time polymerase chain reaction versus direct microscopy, culture, and histology in fungal infections of the nails, scalp, and skin - Vazheva, Gergana; Zisova, Liliya; Miteva‐Katrandzhieva, Tsonka; Dichev, Valentin; Chonov, Veselin (International journal of dermatology, 2023)
BackgroundThe diagnosis of superficial fungal infections is the subject of intensive research in many countries around the world. The diagnostic methods used are diverse, including both conventional and innovative techniques.MethodsThis study evaluates the sensitivity, specificity, and efficacy of the real‐time polymerase chain reaction (PCR) methodology and compares them with those of the conventional methods – direct microscopic, cultural, and histological examinations of materials from hair, skin, and nails – in order to demonstrate the benefits and significance of real‐time PCR for the diagnosis of dermatophytic infections.ResultsThe values obtained for the sensitivity, specificity, and efficacy of direct microscopic, cultural, histological, and real‐time PCR studies are as follows: 63.71, 88.89, and 72.96% (P < 0.001); 58.06, 100, and 73.47% (P < 0.001); 85.96, 100, and 90.70% (P < 0.001); 88.52, 100, and 92.63% (P < 0.001).ConclusionThe use of real‐time PCR in the diagnosis of dermatophytic infections is a relatively new approach in mycology and is subject to testing and experience from its use. The results are promising, but the method has not yet established itself as a new gold standard in the diagnosis of superficial fungal infections caused by dermatophytes, though its application would be very useful in identifying isolates without conidiogenesis or absence of growth.